The Influence of Product Quality, Brand Image and Brand Trust on Consumer Purchase Decisions At Isola Wine Bali - Salimah, Raudhatu; Widiyanti, Marlina; Shihab, Muchsin Saggaff; Wahab, Zakaria (Politeknik Siber Cerdika Internasional, 2025)
This research was conducted with the aim of determining the influence of product quality, brand image and brand trust on consumer purchase decisions at Isola Wine Bali. The population in this study includes all consumers who buy wine, both foreign tourists and locals. The sample used in this study was 100 respondents using the purposive sampling method. The results of multiple linear regression analysis show that product quality, brand image and brand trust have a positive and significant effect on purchase decisions. Product quality, it is hoped that Isola Wine Bali can evaluate the type of wine bottle used. Brand image, it is hoped that adjustments can be made regarding the color of the product packaging which also needs to be adjusted to the color of the bottle of wine products. Brand trust is expected to be able to always provide updated information about the products offered.